Membangun Kemampuan Menjadi Wirausahawan Budi Daya Ikan Serta Produk Olahannya (Studi Pada Yayaysan Rumpun Anak Pesisir (YRAP) Kampung Nelayan Blok Eceng, Muara Angke, Kelurahan Pluit, Kecamatan Penjaringan, Jakarta Utara) - Ignatius Sumbgogo (Universitas Paramadina, 2017)
This paper is structured in order to endorse the activity of community development in developing the ability of becoming fishery cultivation entrepreneur and its derived products in Muara Angke region North Jakarta. Further study is aimed to build the capacity and willingness to develop, organize and manage a business venture along with any of its risks in order to make a profit. The design of this study is qualitative, it causes the data and analysis used in this study is also qualitative. Qualitative research is a study that relates to ideas, perceptions, opinions, beliefs of people to be studied. In qualitative research everything can not be measured by numbers and theories used in the study are not forced to obtain the full picture of a thing according to the human view that has been studied. The results of this program are creativity of students and fishermen in developing marine processed products and aquaculture are increasing, they are able to think critically and innovatively, they are able to solve problems, especially regarding the challenges of environmental problems and they understand the importance of education/school.